AB1237 Diagnostic value of proteasomal and autophagic markers in muscular diseases. (2nd June 2020) - Drott, U.; Harter, P.; Burkhardt, H.; Mittelbronn, M.
Abstract : Background: Deficient cellular degradation pathways such as autophagy and the ubiquitin proteasome system (UPS) show a correlation with the onset of neurodegenerative diseases. Especially immune-mediated inflammatory myopathies often show therapy-resistant phenotypes with medical need for further understanding of pathogenesis und possible treatment. Objectives: The aim of this work was to study an association of these two degradation pathways in a large group of different muscle entities and to examine a possible influence in the pathogenesis of the investigated muscle diseases. Furthermore, a potential benefit in diagnostics was studied using factors such as ubiquitin, p62, NBR1 and LC3 and their role as adapter molecules. Methods: We examined ubiquitin, p62, NBR1 and LC3 on muscle biopsies from patients with the diagnosis of s-IBM, dermato- and polymyositis, muscular dystrophy, neurogenic atrophy, myotonic dystrophy type II (PROMM) and metabolic myopathies such as Pompe and McArdle disease. Immunohistochemical single and double stainings as well as immunofluorescence stainings were performed on cryosections. Furthermore, Western blot analysis was performed. The use of a histological score, defined as the product of the frequency of positive fibres and staining intensity, was used to investigate possible differences between the diseases in the expression of the investigated factors. Results: Especially in s-IBM, myofibrillar myopathies and Pompe disease, proteasomal and autophagic markers were detected. On the other hand, neurogenic atrophy, McArdle disease and the majority of the myotonic dystrophies type II showed no positive signals, except for p62, which was detected especially in internalized nuclei and regenerative fibres. Overall, in all entities in regenerative and necrotic as well as in atrophic fibres, a positive staining for ubiquitin, p62, NBR1 and LC3 could be shown. Dermatomyositis showed a moderate immunoreactivity for p62 and NBR1 in the area of the perifascicular atrophy. Polymyositis showed a strong endomysial reaction in the area of the attacked muscle fibres, especially in the area of the lymphocytic infiltrates. The histological score showed that ubiquitin was significantly higher in s-IBM than in polymyositis. NBR1 was significantly higher in s-IBM than in dermatomyositis and muscular dystrophies. LC3 and p62 showed a significantly higher level in s-IBM as compared to dermatomyositis and polymyositis. Except for NBR1, a positive correlation of autophagic and proteasomal markers was shown in dermatomyositis. There was also a positive correlation between LC3 and ubiquitin in polymyositis. Using multivariate analysis and recursive partitioning, we could show a predictability of the diagnosis of s-IBM with a LC3 score above 3. On the other hand, a value below 3 excluded the diagnosis of s-IBM. Conclusion: In particular, s-IBM, myofibrillar myopathies and Pompe disease showed a possible involvement disturbed proteasomal and autophagic degradation pathways in their pathogenesis. In addition, p62 and NBR1 seemed to have an important role in the immune response. Furthermore, the altered autophagic and proteasomal degradation pathways may be involved in ageing processes, sarcopenia and disease. In particular, LC3 seems to be suitable as a screening marker to recognize an idiopathic inflammatory myopathy. The other markers, such as p62, LC3, and NBR1, would be able to distinguish between the subgroups of idiopathic inflammatory myopathies. Therefore, LC3 could be included as a marker in the routine of neuropathological diagnostics. Further studies are needed to fully understand the role of proteasomal and autophagic factors in possible immune suppressive and immune modulatory therapies and to assess possible side effects. Disclosure of Interests: Ulrich Drott: None declared, Patrick Harter: None declared, Harald Burkhardt Grant/research support from: Pfizer, Roche, Abbvie, Consultant of: Sanofi, Pfizer, Roche, Abbvie, Boehringer Ingelheim, UCB, Eli Lilly, Chugai, Bristol Myer Scripps, Janssen, and Novartis, Speakers bureau: Sanofi, Pfizer, Roche, Abbvie, Boehringer Ingelheim, UCB, Eli Lilly, Chugai, Bristol Myer Scripps, Janssen, and Novartis, Michel Mittelbronn: None declared